1998
DOI: 10.1177/001391659803000502
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Museum Exhibit Design on Immersion and Psychological Flow

Abstract: Two studies were designed to investigate the role of immersing design techniques in determining museum visitors' experience. Study 1 observed visitor behavior in a museum hall at the Denver Museum of Natural History (DMNH) in Denver, Colorado, before and after renovation. The study found that after the design changes, visitors attended more to the exhibits. Study 2, a post hoc survey analysis complementing Study 1, discriminated which particular design features were responsible for eliciting a high degree of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 13 publications
2
29
0
2
Order By: Relevance
“…For example, Mark Harvey and his colleagues have shown that multisensory stimulation, along with interactive components and dynamic displays, has a strong influence on the visitor experience, especially in terms of the visitor's sense of flow and immersion. 2 Another intriguing example can be found at the Jorvik Viking Centre (http://jorvik-viking-centre.co.uk), where multisensory stimuli is used to enrich the experience of a tour concerning the Viking past of the city of York. This experience lets the visitor touch historical objects (Viking Age artifacts); taste the unsalted, dried cod of the Viking diet; smell the aroma of the corresponding displayed objects; see the animals and inhabitants of the Viking city; and listen to the Viking sagas.…”
Section: Multisensory Designmentioning
confidence: 99%
“…For example, Mark Harvey and his colleagues have shown that multisensory stimulation, along with interactive components and dynamic displays, has a strong influence on the visitor experience, especially in terms of the visitor's sense of flow and immersion. 2 Another intriguing example can be found at the Jorvik Viking Centre (http://jorvik-viking-centre.co.uk), where multisensory stimuli is used to enrich the experience of a tour concerning the Viking past of the city of York. This experience lets the visitor touch historical objects (Viking Age artifacts); taste the unsalted, dried cod of the Viking diet; smell the aroma of the corresponding displayed objects; see the animals and inhabitants of the Viking city; and listen to the Viking sagas.…”
Section: Multisensory Designmentioning
confidence: 99%
“…The survey is usually qualified as a regular method of measuring the optimal forms of experience. Surveys are administered within particular populations, for example, the subscribers to a special group of online services, visitors of some website(s), learners of a certain software product (Ghani & Deshpande, 1994;Harvey, Loomis, & Bell, 1998;Konradt, Filip, & Hoffmann, 2003;Koufaris, 2002;Skadberg & Kimmel, 2004;Trevino & Webster, 1992;Webster, Trevino, & Ryan, 1993). This style of surveying can be called retrospective because it refers to a habitual behavior, related to the cyberspace, to a favorite type of web source, or to a known software product (Huang, 2006;Korzaan, 2003;Montgomery, Sharafi, & Heidman, 2004;Sharafi, Heidman, & Montgomery, 2006).…”
Section: Data Collection Methods In the Optimal Experience Studies Rementioning
confidence: 99%
“…The notion of displaying the specimen thus serves as an example of an exhibition strategy favoured for its traditional closeness to the scientific context. The science centre staff, on the other hand, felt that due to the beetle's small size and the lack of any inherent interactivity in a specimen display, such a display would be of relatively little interest to visitors (EE3); a point of view which is supported by research (Bitgood, Patterson, & Benefield, 1988;Harvey, Loomis, Bell, & Marino, 1998). Therefore, from the point of view of the science centre, the idea of exhibiting the specimen did not intersect with any visitor-related, i.e.…”
Section: Example 1: the Display Of Specimensmentioning
confidence: 99%